COVID 19 pandemic: Effect on management of patients with breast cancer; single center retrospective cohort study. (September 2021) - Mooghal, Mehwish; Javaid, Rana Hassan; Khan, Wajiha; Muneeb, Muhammad; Khan, Waseem Ahmad; Ahmad, Asrar; Barohi, Lal Bux; Rahim, Kamran; Tahseen, Hina; Gul, Amna
Abstract: Background: (SARS-COV-2) infection, led to a pandemic affecting many countries, resulting in hospitals diverting most of their resources to fight the pandemic. Breast cancer, already a healthcare dilemma, is also affected in this scenario. Our aim was to find out the impact of COVID-19 on presentation of breast cancer stage and its effects on overall onco-surgical management. Methods: This cohort single-centered retrospective review was carried out at our hospital, over a period of 18 months. Females with known breast cancer were included in the study. Data was collected on performas by a single researcher. Effect of COVID pandemic on presentation stage and its impact on overall management was studied. SPSS 23.0 used for data analysis. A 95% CI was used. Descriptive statistics were presented as range/means. Categorical data was analyzed by Fisher exact test, t -test was applied to numerical data, p value ≤ 0.05 was considered significant. Results: Out of 87 patients presenting with suspicious lump, 69 who had malignancy on histo-pathology were included in study. Twelve out of 69 were COVID positive. Sixty patients presented with advanced stage (≥stage 2b) out of which 21 underwent upstaging of disease due to delay in presentation/management. We found that 9 out of 12 (majority) Covid positive patients had disease upstaging. Overall main reason for delay in presentation was found to be unawareness of disease. Conclusion: We concluded that COVID-19 pandemic had no impact on presentation delay, breast cancer management/treatment and disease upstaging as compared to figures available for our population before the pandemic. However, our study showed significant correlation between disease upstaging and COVID status. This led us to reconsider our preformed protocols for COVID positive breast cancer patients. Our results can be used by future researchers to investigate if COVID itself can contributes in patho-physiology of upstaging in breast cancer or not. Highlights: Covid 19 pandemic has no impact on presentation and management of Breast Cancer in our population. During covid-19 lockdown, Breast Cancer patients presented with advanced stage of the disease. Unawareness still outnumbered all the other factors responsible for delayed presentation in our population. Covid status has significant impact on disease upstaging, however little data is available in this domain.